Computer Supported Cooperative Work Systems. Continued Examinations - Wójtowicz, Radosław (Advanced Information Technologies for Management – AITM 2008, 2008)
The article is the short introduction to the questions relating to the teamwork and software which supports collaborative work. The main goal of the presented article is the introduction to the forecoming research on a wide class of groupware software. In the article also a synthetic comparative analysis of the current research and the previous studies has been made. It allowed the author to draw certain conclusions of general nature concerning development trends that are taking place.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 177-183